Forest Degradation Impact on Soil Organic Carbon - A Geospatial Approach - Singh, S.P.; Kumar, S.; Singh, Sarnam; Hussin, Y. (Indian Forester, 2022)
Soil organic carbon (SOC) is one of the soil health indicators. Forest soils are negatively impacted by biotic interference and the authors impact from forest canopy cover amenable to Earth Observation data. We mapped forest cover types and canopy density using remote sensing data. Sample design and size were based on the stratification and homogeneity map. The soil samples were collected from three depths using the pit method for analysis and SOC stock estimation. A linear and positive correlation between SOC and forest cover density was observed, indicating the negative impact of forest degradation on SOC. The maximum SOC stock of 61.16 ± SE3.96 Mg ha-1 was observed in top 30 cm soil in Sal forests with >80% canopy density and minimum (25.64 Mg ha-1) in Sal-mixed Teak forests with 40-60% canopy density. Total SOC ranged from 68.98 ± SE11.38 Mg ha-1 in the Hill Sal forest with 10-40% canopy density to 179.05 ± SE11.20 Mg ha-1 in pure Sal forests with >80% canopy density. It revealed that forest canopy degradation due to biotic interference caused loss of SOC in almost all the soil layers. SOC geospatial map shows areas for protection and reforestation/enrichment planting to enhance soil carbon stock.